Artificial nest predation rates vary depending on visibility in the eastern Brazilian Amazon - Michalski, Fernanda; Norris, Darren (Acta Amazonica, 2014)
Observational and experimental studies have shown that increased concealment of bird nests reduces nest predation rates. The objective of the present study was to evaluate differences in predation rates between two experimental manipulations of artificial ground nests (i.e., clearing an area around the artificial nest or leaving it as natural as possible), and test whether environmental variables also affected nest predation in an undisturbed area of Amazonian forest in eastern Brazil. A generalized linear model was used to examine the influence of five variables (manipulation type, perpendicular distance from the main trail, total basal area of trees surrounding the nest site, understorey density, and liana quantity) on nest predation rates. Model results, showed that manipulation type was the only variable that significantly affected nest predation rates. Thus, to avoid systematic biases, the influence of nest site manipulation must be taken into consideration when conducting experiments with artificial nests.
Taxas de predação em ninhos artificiais variam dependendo da visibilidade na Amazônia Oriental Brasileira
Keywords: Experimental Manipulation; Potential Biases; Quail Egg; Manipulação Experimental; Potenciais Vieses; Ovo De Codorna